Does physical activity associate with gut microbiome and survival outcomes of Chinese metastatic colorectal cancer patients? A secondary analysis of a randomized controlled trial - Lingyun Sun; Yunzi Yan; Shaohua Yan; Yufei Yang (Heliyon, 2022)
Background: This study aimed to evaluate associations between physical activities, gut microbiome and survival outcomes among Chinese metastatic colorectal cancer (mCRC) patients. Methods: We conducted a secondary analysis nested in a randomized controlled clinical trial (RCT) of a traditional Chinese herbal medicine for mCRC patients (ChiCTR2000029599). After one-month intervention, we followed up patients every six months for survival outcomes and the last follow-up was in August 2022 (median follow-up time 28.6 months). We assessed patients’ physical activity (PA) through short form of the International Physical Activity Questionnaire (IPAQ-SF) and collected patients’ stool samples at baseline. Kaplan–Meier survival analyses and Cox regression models were used to evaluate the association between PA level and overall survival outcomes. 16S rRNA sequencing approaches were utilized for the gut microbiome analysis. Results: Among 40 mCRC patients enrolled in the original RCT, 15 patients were still alive at the time of the last follow-up. The mean IPAQ score was 2569.5 MET-min/week for all patients, indicating a moderate PA level. Specifically, there were 7 patients in high PA level group, 2 patients in low PA level group and the rest were in middle PA group. Gut microbiome community difference analysis showed that patients with high PA levels had a significantly higher alpha diversity than that of the middle PA group (131.53 vs. 98.12, p = 0.04), an increased abundance of Phascolarctobacterium and Ruminococcaceae and a decreased abundance of Megasphaera at the genus level. Cox regression model showed that after controlling for the original tumor site and TCM treatment, high PA level was independently associated with a lower risk of death (relative risk 0.13, p = 0.014). Conclusions: High PA level could be associated with survival benefits among Chinese mCRC patient through its potential role on modulating gut microbiome. Our results could be referred to patients’ education and future clinical study design.